Quality Improvement of Salt Products in Cambodia - Huon, Sorangsey; Yat, Yat; Cham, Souen (Journal of Applied Research and Innovation (JARI), 2026)
The study examined the betterment of salt production, focusing on the quality, salt marketing, salt strategy-planning, and salt-quality sustainability. This study mostly focused on the key aspects of enhancing the salt production, such as quality, quantity, and sustainability of salt production in Cambodia. This study employed the qualitative research design to collect and analyze the data through secondary data analysis. The study highlighted the quality development of salt production and salt strategy-planning. The results of the SWOT analysis focus on the sustainability of salt production and salt marketing in Cambodia. The study also argued that the salt marketing transformation in terms of increasing the quality and quantity of salt production. This study proffered the potential contributions of designing an effective strategy-planning, salt-marketing transformation, trends of the salt production, and salt-production sustainability.